Gamification: Methodology to Engage and Motivate Students in the Learning Process - Inés ARAÚJO (Ediciones Universidad de Salamanca, 2016)
Gamification is a recent concept and is projected as a technological trend to implement in schools by 2017 (Johnson, Adams Becker Road & Freeman, 2014a, 2014b, 2014c). Currently the majority of application examples of Gamification, including the educational context, are to use Buttons / Badges, Leaderboards and Scores. Several authors (Burke, 2014; Deterding, 2014; Kapp, 2012; Zichermann, 2013) emphasize that the Gamification cannot be restricted to the mere application of these game mechanics into any contexts wanted to be gamified. It is necessary to know the interests of the audience, their needs, what can motivate them and plan a gamify activity that meets these expectations. For all these reasons is important to develop studies to understand how this process could be implemented more effectively in educational contexts, enabling the development of appropriate tools and creating guidelines that can guide those who want to include Gamification in their teaching practice. This article presents a literature review on the concept of Gamification, describing some relevant examples that make it easier to understand how it can be implemented, proposing questions to ponder when applying this new methodology to educational contexts.